Good practice recommendations for the use of time-lapse technology†. Issue 2 (19th March 2020) - ,; Apter, Susanna; Ebner, Thomas; Freour, Thomas; Guns, Yves; Kovacic, Borut; Le Clef, Nathalie; Marques, Monica; Meseguer, Marcos; Montjean, Debbie; Sfontouris, Ioannis; Sturmey, Roger; et al.
Abstract: STUDY QUESTION: What recommendations can be provided on the approach to and use of time-lapse technology (TLT) in an IVF laboratory? SUMMARY ANSWER: The present ESHRE document provides 11 recommendations on how to introduce TLT in the IVF laboratory. WHAT IS KNOWN ALREADY: Studies have been published on the use of TLT in clinical embryology. However, a systematic assessment of how to approach and introduce this technology is currently missing. STUDY DESIGN, SIZE, DURATION: A working group of members of the Steering Committee of the ESHRE Special Interest Group in Embryology and selected ESHRE members was formed in order to write recommendations on the practical aspects of TLT for the IVF laboratory. PARTICIPANTS/MATERIALS, SETTING, METHODS: The working group included 11 members of different nationalities with internationally recognized experience in clinical embryology and basic science embryology, in addition to TLT. This document is developed according to the manual for development of ESHRE recommendations for good practice. Where possible, the statements are supported by studies retrieved from a PUBMED literature search on 'time-lapse' and ART. MAIN RESULTS AND THE ROLE OF CHANCE: A clear clinical benefit of the use of TLT, i.e. an increase in IVF success rates, remains to be proven. Meanwhile, TLT systems are being introduced in IVF laboratories. The working group listed 11 recommendations on what to do before introducing TLT in the lab. These statements include an assessment of the pros and cons of acquiring a TLT system, selection of relevant morphokinetic parameters, selection of an appropriate TLT system with technical and customer support, development of an internal checklist and education of staff. All these aspects are explained further here, based on the current literature and expert opinion. LIMITATIONS, REASONS FOR CAUTION: Owing to the limited evidence available, recommendations are mostly based on clinical and technical expertise. The paper provides technical advice, but leaves any decision on whether or not to use TLT to the individual centres. WIDER IMPLICATIONS OF THE FINDINGS: This document is expected to have a significant impact on future developments of clinical embryology, considering the increasing role and impact of TLT. STUDY FUNDING/COMPETING INTEREST(S): The meetings of the working group were funded by ESHRE. S.A. declares participation in the Nordic Embryology Academic Team with meetings sponsored by Gedeon Richter. T.E. declares to have organized workshops for Esco and receiving consulting fees from Ferring and Gynemed and speakers' fees from Esco and honorarium from Merck and MSD. T.F. received consulting fees from Vitrolife and Laboratoires Genévrier, speakers' fees from Merck Serono, Gedeon Richter, MSD and Ferring and research grants from Gedeon Richter and MSD. M.M. received sponsorship from Merck. M.M.E. received speakers' fees from Merck, Ferring and MSD. R.S. received a research grant from ESHRE. G.C. received speakers' fees from IBSA and Excemed. The other authors declare that they have no conflict of interest. TRIAL REGISTRATION NUMBER: N/A. DISCLAIMER: This Good Practice Recommendations (GPR) document represents the views of ESHRE, which are the result of consensus between the relevant ESHRE stakeholders and are based on the scientific evidence available at the time of preparation . ESHRE's GPRs should be used for information and educational purposes. They should not be interpreted as setting a standard of care or be deemed inclusive of all proper methods of care nor exclusive of other methods of care reasonably directed to obtaining the same results. They do not replace the need for application of clinical judgment to each individual presentation, nor variations based on locality and facility type . Furthermore, ESHRE GPRs do not constitute or imply the endorsement, or favouring of any of the included technologies by ESHRE . † ESHRE Pages content is not externally peer reviewed. The manuscript has been approved by the Executive Committee of ESHRE.